2004
DOI: 10.1242/jcs.01473
|View full text |Cite
|
Sign up to set email alerts
|

Fkh2p and Sep1p regulate mitotic gene transcription in fission yeast

Abstract: In the fission yeast Schizosaccharomyces pombe, several genes including cdc15+, spo12+, fin1+, slp1+, ace2+ and plo1+ are periodically expressed during M phase. The products of these genes control various aspects of cell cycle progression including sister chromatid separation, septation and cytokinesis. We demonstrate that periodic expression of these genes is regulated by a common promoter sequence element, named a PCB. In a genetic screen for cell cycle regulators we have identified a novel forkhead transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 44 publications
9
94
1
Order By: Relevance
“…We have shown that deletion of the five repeats eliminated ace2 ϩ transcription and function, indicating that they are important for ace2 ϩ expression. Interestingly, two of these sites (at Ϫ375 base pairs and Ϫ220 base pairs) are located 8 and 15 nt downstream of the GCAAC G / A sequence (the PCB element), which is the binding site for the MADS box protein Mbx1p (Buck et al, 2004). These authors have proposed that Mbx1p might form a complex with Sep1p and a second forkhead-like factor, Fkh2p, to control periodic gene transcription in M phase.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that deletion of the five repeats eliminated ace2 ϩ transcription and function, indicating that they are important for ace2 ϩ expression. Interestingly, two of these sites (at Ϫ375 base pairs and Ϫ220 base pairs) are located 8 and 15 nt downstream of the GCAAC G / A sequence (the PCB element), which is the binding site for the MADS box protein Mbx1p (Buck et al, 2004). These authors have proposed that Mbx1p might form a complex with Sep1p and a second forkhead-like factor, Fkh2p, to control periodic gene transcription in M phase.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in septum formation, cytokinesis, nuclear structure and mitotic spindle function (Bulmer et al, 2004). It was also suggested that Fkh2 was implicated in the periodic gene expression of M and G1 phases (Buck et al, 2004), (when it is phosphorylated (Buck et al, 2004)) by negatively regulating the transcription of a cluster of genes (Rustici et al, 2004). The null mutant displays longer length, coldsensitive, heat-sensitive and slow-growing phenotypes (Buck et al, 2004), (Bulmer et al, 2004).…”
Section: Forkhead Transcription Factorsmentioning
confidence: 99%
“…It was also suggested that Fkh2 was implicated in the periodic gene expression of M and G1 phases (Buck et al, 2004), (when it is phosphorylated (Buck et al, 2004)) by negatively regulating the transcription of a cluster of genes (Rustici et al, 2004). The null mutant displays longer length, coldsensitive, heat-sensitive and slow-growing phenotypes (Buck et al, 2004), (Bulmer et al, 2004). Regarding meiosis, a null mutant presents low levels of ste11 mRNA, dephosphorylation at Fkh2 residues T314 and S462 is required for binding to ste11 promoter region and induction of ste11 transcription during nitrogen starvation (Shimada et al, 2007).…”
Section: Forkhead Transcription Factorsmentioning
confidence: 99%
“…As in budding (Zilahi et al, 2000;Buck et al, 2004;Bulmer et al, 2004). Two of these, Fkh2p and Mbx1p, are phosphoproteins, whose phosphorylation status varies through the cell cycle peaking in late M-phase, with genetic experiments implying a role for the Polo protein kinase Plo1p (Anderson et al, 2002;Buck et al, 2004;Bulmer et al, 2004). In this paper we examine how this transcription factor complex is regulated, and reveal a role for phosphorylation of Mbx1p by Plo1p, together with cell-cyclespecific binding by Fkh2p, Sep1p and Plo1p to PCB promoters.…”
Section: Introductionmentioning
confidence: 95%
“…The products of these genes regulate spindle formation, the onset of anaphase, the formation and placement of the actomyosin ring and cytokinesis. As in budding (Zilahi et al, 2000;Buck et al, 2004;Bulmer et al, 2004). Two of these, Fkh2p and Mbx1p, are phosphoproteins, whose phosphorylation status varies through the cell cycle peaking in late M-phase, with genetic experiments implying a role for the Polo protein kinase Plo1p (Anderson et al, 2002;Buck et al, 2004;Bulmer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%